Answer: A. 2x2 - 3x - 8
Just subtract the functions and combine like terms
(f - g)(x) = f(x) - g(x)
(f - g)(x) = 2x^2 - 5 -(3x + 3)
(f - g)(x) = 2x^2 - 5 - 3x - 3
(f - g)(x) = 2x^2 - 3x - 8
First you need to know how much each guest will eat
Answer:
odd
Step-by-step explanation:
i looked it up
Answer:
Step-by-step explanation:
Check if the lengths of the sides follows the Pythagorean theorem.
9² + 12² ≟ 15²
81 + 144 ≟ 225
225 = 225
Triangle ABC is a right triangle.
-3 is in the opposite direction of V